Desinformación visual en redes sociales y medios digitales: una propuesta taxonómica de la manipulación fotográfica distribuida durante la pandemia. - Muñiz-Velázquez, Jose Antonio; Navazo-Ostúa, Pablo (CIC. Cuadernos de Información y Comunicación, 2021)
This article presents an approach to the phenomenon of visual disinformation with the intention of developing a taxonomy that classifies the techniques used in the production of false images in disinformative content related to COVID-19. Based on a sample of 80 items of visual disinformative content related to the pandemic and its social consequences, extracted from informative websites, digital media and social networks. An inductive process has been developed on the sample in four phases: firstly, a collection and tracking, followed by the observation and interpretation of its contents, to classify them and finally obtain common referential patterns that can be extrapolated. In this way, we seek to establish current patterns that allow us to catalogue the techniques and processes of photographic manipulation. As a result, a taxonomy proposal has been obtained as a map of the tactics that have been mainly used for visual disinformation during the pandemic. Three primary classificatory segments are established: ex ante, ex facto and ex post manipulations, alluding to the time period in which the alteration of the (dis)informative photograph takes place. Finally, a second classificatory arrangement arises according to the exact typology of the manipulative technique employed. In conclusion, the role of photography in the disinformation that affects the current pandemic crisis is evident, highlighting the various manipulative paths that the image can take. The proposal aims to contribute to the desire of those who, in the face of this double pandemic, viral and disinformative, see the opportunity to reinforce a stronger media literacy.
Keywords: Disinformation; social networks; infodemic; COVID-19; photography; visual comunicación; visual fake